Review hasil penelitian: Analisis model kepuasan pembelajaran online pada fakultas ilmu tarbiyah dan keguruan Indonesia selama pandemi covid-19 - shoimah, Dewi (Maliki Interdisciplinary Journal, 2024)
The sudden change from offline learning to online learning using e-Learning began since the outbreak of the Covid-19 Pandemic. This is a new thing for most students and lecturers at the Faculty of Tarbiyah and Teacher Training (FITK) State Islamic University in Indonesia. This learning is also an important requirement that must be taken to complete their university education. There are several challenges faced in the learning system through e-Learning, namely the quality of the e-Learning system and the quality of online learning by lecturers. This challenge has an impact on the satisfaction and benefits felt by students and lecturers themselves.